A Primary Hepatic Lymphoma Treated with Liver Resection and Chemotherapy - Konstantinos Bouliaris; Grigorios Christodoulidis; Georgios Koukoulis; Ioannis Mamaloudis; Maria Ioannou; Eleni Bouronikou; Maria Palassopoulou; Konstantinos Tepetes (Case Reports in Surgery)
Primary hepatic lymphoma (PHL) is a rare malignancy, which is frequently misdiagnosed. Although chemotherapy is the treatment of choice there are reports that a combination of surgery and adjuvant chemotherapy can offer better results. Herein we present an interesting case of a large primary non-Hodgkin lymphoma originating from liver was treated with a liver which resection and chemotherapy.